Pengurangan Sortir dan Return Produk Sauce Pack Topact sebagai Strategi Industri Hijau di Industri Flexible Packaging - Ali Mustofa (Kreator, 2025)
The flexible packaging manufacturing industry faces significant challenges related to product quality, resulting in high sorting and return rates and impacting smooth delivery. High return rates are a major concern as they not only reduce customer satisfaction but also impact the achievement of the company's Key Performance Indicators (KPIs) of On-Time Delivery and Zero Returns. Initial analysis showed that the slitting process was a critical point in the flexible packaging production process, with two main problems, namely a messy roll and a narrow paper core. These two problems were the largest contributors to the number of customer sorting and returns. To overcome these, the company implemented two approaches, first by eliminating the technical causes of both problems, and second by preventing the problems from being passed on to customers, while reducing waste and potential environmental pollution using fishbone diagrams and root cause analysis methods. The implementation results showed significant improvements. The average monthly sorting rate decreased from 18 rolls to 7 rolls and returns were reduced from 6 rolls to 0 rolls between May 2025 and September 2025. Through Continuous Improvement efforts, the company successfully addressed issues with messy rolls and narrow paper cores that previously led to product returns and quality degradation. With measurable and documented steps, the company not only optimized its production processes but also significantly improved customer satisfaction. This success reflects the company’s commitment to quality and sustainability, efficient and environmentally friendly operations.